The Planning Polity - Tewdwr-Jones, Mark (Taylor and Francis, 2003)
Planning is not a technical and value free activity. Planning is an overt political system that creates both winners and losers. The Planning Polity is a book that considers the politics of development and decision-making, and political conflicts between agencies and institutions within British town and country planning. The focus of assessment is how British planning has been formulated since the early 1990s, and provides an in-depth and revealing assessment of both the Major and Blair governments' terms of office. The book will prove to be an invaluable guide to the British planning system today and the political demands on it. Students and activists within urban and regional studies, planning, political science and government, environmental studies, urban and rural geography, development, surveying and planning, will all find the book to be an essential companion to their work